Durable compliant electrode based on graphene and natural rubber. Issue 2 (28th July 2016) - Korattanawittaya, Sasithorn; Petcharoen, Karat; Sangwan, Watchara; Tangboriboon, Nuchnapa; Wattanakul, Karnthidaporn; Sirivat, Anuvat
Abstract : A compliant electrode is a stretchable electronic device that retains good conductivity under stretching or bending. It has been used in various electro‐actuating applications which require large deformations under electrical field. The objective of this work was to fabricate a compliant electrode possessing high electrical conductivity and good mechanical properties. Due to the excellent mechanical properties of natural rubber (NR), it was used as a matrix for the compliant electrode. Graphene was used as a new and innovative conductive filler to provide excellent electrical conductivity. The mechanical properties and electrical properties were investigated by using a rheometer in the tension mode. Both mechanical and electrical properties were improved drastically by introducing graphene into the matrix. The highest electrical conductivity of 0.61 S/cm was obtained from the 35.0 %vol/vol graphene/NR composite, two orders of magnitude higher than that of the commercial compliant electrode. The 5.0 %vol/vol graphene/NR composite was shown and identified here as a promising material for using as a compliant electrode. POLYM. ENG. SCI., 57:129–136, 2017. © 2016 Society of Plastics Engineers